Probiotic potential of Lactobacillus strains with antimicrobial activity against some human pathogenic strains - Shokryazdan, Parisa; Sieo, Chin Chin; Kalavathy, Ramasamy; Liang, Juan Boo; Mohamed Alitheen, Noorjahan Banu; Jahromi, Mohammad Faseleh; Ho, Yin Wan (Hindawi Publishing Corporation, 2014)
The objective of this study was to isolate, identify, and characterize some lactic acid bacterial strains from human milk, infant feces, and fermented grapes and dates, as potential probiotics with antimicrobial activity against some human pathogenic strains. One hundred and forty bacterial strains were isolated and, after initial identification and a preliminary screening for acid and bile tolerance, nine of the best isolates were selected and further identified using 16 S rRNA gene sequences. The nine selected isolates were then characterized in vitro for their probiotic characteristics and their antimicrobial activities against some human pathogens. Results showed that all nine isolates belonged to the genus Lactobacillus. They were able to tolerate pH 3 for 3 h, 0.3% bile salts for 4 h, and 1.9 mg/mL pancreatic enzymes for 3 h. They exhibited good ability to attach to intestinal epithelial cells and were not resistant to the tested antibiotics. They also showed good antimicrobial activities against the tested pathogenic strains of humans, and most of them exhibited stronger antimicrobial activity than the reference strain L. casei Shirota. Thus, the nine Lactobacillus strains could be considered as potential antimicrobial probiotic strains against human pathogens and should be further studied for their human health benefits.